Comparative analysis of income between fishing businesses with bottom longlines and floating traps in Sanga-Sanga Sub District Kutai Kartanegara District - Sudewi Sudewi; Helminuddin Helminuddin; Fitriyana Fitriyana; Said Abdusysyahid (Depik, 2025)
The fishing business in Sanga-Sanga Sub-district is carried out by fishermen who use different fishing gear such as basic longline and floating bubu. This study aimed to analyze the income from the fishing business by basic longline fishermen and floating bubu and whether there is a real difference between the income of basic longline fishermen and floating bubu. Based on the analysis result, it was known that the average income of fishermen who use basic longlines was Rp 46,579,291.67/year while fishermen who use floating bubu is Rp 9,963,200.00/year. The statistical analysis results of the unpaired two-sample t-test showed that the calculated t value was 5.905 greater than the t table value of 2.447 and had a significance value of the t test which was smaller than 0.05. This meant that there was a significant difference in income between basic longline fishermen and floating bubu fishermen.Keywords:Financial AnalysisFishing GearIncome DifferencesKutai Kartanegara